The Emergence Of Multiculturalism And Intolerance And Its Social-Philosophical Consequences - Kholikov Yunus Ortiqovich (Zien Journals, 2025)
This article reveals that, unlike the term intolerance, which exists in society in parallel with the concept of “tolerance”, in many scientific literature it is called “intolerance”. The importance of studying the negative impact of intolerance on personal development, which hinders the development of a culture of tolerance in young people, and combating the ways in which it affects social groups and strata is studied.
Keywords: Multiculturalism; paradigm; tolerant; tolerance